New methods for complex molecule synthesis - Dawood, Rafid Saad (2018)
This thesis is split into three chapters describing syntheses of two types of the pyrrolidine chemical scaffolds and total synthesis of the natural product (+)-monomorine. The first chapter of this work presents a simple and efficient asymmetric synthesis of novel sp3-rich pyrrolidine chemical scaffolds over five steps starting from simple ketones. The key step includes using tert-butanesulfinamide as a chiral auxiliary to achieve an asymmetric Tsuji-Trost allylation. Following this, cross-metathesis coupling of allyl derivatives with an acrylate ester affords α,β-unsaturated esters. Reduction of the sulfinimine stereoselectively results in the corresponding amide derivatives. The sulfinamides were then employed to synthesise a range of pyrrolidine scaffolds via cyclisation under basic conditions. Finally, by removing the directing group and functionalising the ester group, the resulting scaffold core can be further derivatised. In the second chapter, some of the chemistry of pyrrolidine chemical scaffold that was achieved in the first chapter is used towards an attempted total synthesis of (+)-monomorine, a natural product isolated from the pharaoh ant (Monomorium pharaonis L). In addition, different synthetic routes have been employed as well towards achieving this synthesis. The third and last chapter of this thesis outlines the first attempts to synthesise the spiro-pyrrolidine scaffold starting from 4-bromobutene or 1,7-dichloroheptan-4-one. This type of chemical scaffold will be useful as a versatile intermediate for drug discovery via diversification at three different points on N atoms. The synthetic route required preparation of protected azocan-5-one (eight-membered ring) as a key material in this route. Different reaction conditions have been attempted; involving investigations into the catalyst, temperature, base, stoichiometry and reaction time. It was observed that the cyclisation to give the desired eight-membered ring is very slow and the yield was low.